Pengetahuan Keluarga tentang Pembebasan Pasung - Imam Sunarno; Yayuk Endah Suryani (STIKes Patria Husada Blitar, 2017)
Shelter is an action that uses binding or isolation. In the city of Blitar the number of ODGJ as many as 447 people, while in the village of Kepanjen Kidul there are 117 people with mental disorders, 3 of which carried pemasungan. Good knowledge will make the deprivation of shelter action. The purpose of the study illustrates the family knowledge about the release of ODGJ stalks in the working area of UPTD Pukesmas Kepanjen Kidul Kota Blitar. This research method using descriptive design. The population in this study is the family who has severe mental disorder as many as 117 people and the sample size is 30 people with purposive sampling technique. Data collection was done by using questionnaire. The data were collected on January 28 - March 31, 2017. The research results showed that family knowledge was less than 76.7%. Recommendations for UPTD Pukesmas Kepanjenkidul and cadres as sources of information and expected mental cadres and health workers to provide KIE to ODGJ families about the liberation of the pavement to reduce and prevention of shelter action.